2013
DOI: 10.1007/s10120-013-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study using an infrared imaging system in prevention of post-endoscopic submucosal dissection ulcer bleeding

Abstract: The IRI system detects visible vessels (VVs) that are in no need of coagulation as blue points, and VVs have a potential risk of bleeding as gray points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In addition to ensuring these measures, we believe that some additional measures would be required in patients with large resected specimens or lesions in the L segment and younger patients, who were found in this study to be more prone to postoperative bleeding. For example, it is necessary to identify blood vessels at the ulcer base after ESD, that are prone to cause postoperative bleeding, using endoscopic Doppler ultrasound or infrared imaging system [ 33 , 34 ], and to use over-the-scope-clip for cerclage of the ESD ulcer and medical adhesives for covering the ulcer [ 35 , 36 ]. As these devices and drugs have been examined in only a small number of patients, further study is desired.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ensuring these measures, we believe that some additional measures would be required in patients with large resected specimens or lesions in the L segment and younger patients, who were found in this study to be more prone to postoperative bleeding. For example, it is necessary to identify blood vessels at the ulcer base after ESD, that are prone to cause postoperative bleeding, using endoscopic Doppler ultrasound or infrared imaging system [ 33 , 34 ], and to use over-the-scope-clip for cerclage of the ESD ulcer and medical adhesives for covering the ulcer [ 35 , 36 ]. As these devices and drugs have been examined in only a small number of patients, further study is desired.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators, therefore, have developed methods to try to identify vessels that have a low risk of bleeding. One method uses infrared imaging 49. Yoshida et al49 classified nonbleeding visible vessels a blue or gray points using this system and water-jet pressure was applied to an artificial ulcer base to induce iatrogenic bleeding.…”
Section: Preventing Esd-related Bleedingmentioning
confidence: 99%
“…One method uses infrared imaging 49. Yoshida et al49 classified nonbleeding visible vessels a blue or gray points using this system and water-jet pressure was applied to an artificial ulcer base to induce iatrogenic bleeding. Vessels with blood flow were dark gray from infrared absorption by hemoglobin; coagulated vessels were blue.…”
Section: Preventing Esd-related Bleedingmentioning
confidence: 99%
“…A different approach to lessen post-ESD bleeding was taken by Yoshida et al [17] to detect the nonbleeding visible vessels effectively by use of an infrared imaging system. They revealed that blue points did not need coagulation and gray points had a potential risk of bleeding and needed preventative hemostasis.…”
Section: Complications and Their Preventionmentioning
confidence: 99%